The Effects of Dexamethasone on the Response of Bronchus-associated Lymphoid Tissue to Intranasal Administration of Formalin-killed Pasteurella haemolytica A2 in Goats - Saad, Mohd Zamri; Abdul Wahid, Mohd Effendy (Elsevier Science Publishers, 1999)
A trial was conducted to observe the immediate and chronic e¡ects in goats of dexamethasone administration on the bronchus-associated lymphoid tissue (BALT) response to intranasal administra- tion of formalin-killed Pasteurella haemolytica A2. Twenty-four goats were divided into four groups. Those in group 1 were injected intramuscularly with 1 mg/kg dexamethasone on three consecutive days, followed by intranasal exposure to formalin-killed P. haemolytica A2 one day after the last dexamethasone treatment. The goats in group 2 were similarly injected with dexamethasone followed by intranasal exposure to formalin-killed P. haemolytica A2 21 days after the last dexamethasone treatment. The animals in group 3 were exposed intranasally to formalin-killed P. haemolytica A2 without prior dexamethasone treatment. The animals in group 4 were untreated controls. The intranasal exposures to formalin-killed P. haemolytica A2 were repeated 2 weeks later. Intranasal exposure to formalin-killed P. haemolytica 1 day after dexamethasone treatment further reduced the number and size of BALT compared to the untreated control. Signi¢cantly (p50.01) more reduction of BALT occurred in goats exposed to formalin-killed P. haemolytica A2 21 days after dexamethasone treatment. On the other hand, intranasal exposure of goats without prior dexamethasone treatment stimulated the BALT compared to the untreated controls.